The Relationship Between Personal Hygiene with Hepatitis a Incident in Students - Dwika Sari Sasoka; Prijono Satyabakti (Jurnal Berkala Epidemiologi, 2014)
The prevalence and distribution of hepatitis A cases in recent years in Indonesia have increased. This causes Indonesia to be included in a country with Hepatitis endemic status. The purpose of this study was to analyze the relationship between individual hygiene and the incidence of Hepatitis A in Jember District. The study was conducted on students in educational institutions in the Jember District with an extraordinary case of Hepatitis A in 2013. This study used a case-control design with a quantitative analytic approach. The population of this research is students in educational institutions. Case respondents were selected using simple random sampling and control respondents were selected using purposive sampling. The number of respondents was 15 case respondents and 30 control respondents. The independent variable is the personal hygiene behavior of the respondents. The analysis was performed by the Chi-square test with a Confidence Interval (CI) of 95%. The results showed that the majority of respondents in the case group had poor personal hygiene behavior (53.3%) and the majority of the control group had good personal hygiene (83.3%). Chi-square test showed an association between personal hygiene and the incidence of Hepatitis A (p = 0.016; OR = 5.71; 95% CI = 1.17–2.15). The conclusion is that personal hygiene on the host is related to the incidence of Hepatitis A. It is recommended to increase awareness to maintain personal hygiene by implementing clean and healthy live behaviors.